2021
DOI: 10.1016/j.ejim.2021.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of biliary drainage of malignant biliary obstruction due to colorectal cancer metastases: A systematic review

Abstract: Background and aims: Malignant biliary obstruction is an ominous complication of metastatic colorectal cancer (mCRC). Biliary drainage is frequently performed to relieve symptoms of jaundice or enable palliative systemic therapy, but effective drainage can be difficult to accomplish. The aim of this study is to summarize literature on clinical outcomes of biliary drainage in mCRC patients with malignant biliary obstruction. Methods: We searched Medline and EMBASE for studies that included patients with maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(140 reference statements)
0
4
0
Order By: Relevance
“…Bile duct dilation is an indirect sign of gallbladder cancer, which is triggered by bile duct compression, tumor invasion of the common bile duct, and tumor spread through the bile duct [ 14 ]. Low biliary tract obstruction is caused by bile duct dilation causing stones to enter the lower common bile duct, and high biliary tract obstruction is caused by Mirizzi syndrome [ 15 , 16 ]. Patients with chronic cholecystitis are less likely to have high or low obstruction because of the absence of bile duct dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Bile duct dilation is an indirect sign of gallbladder cancer, which is triggered by bile duct compression, tumor invasion of the common bile duct, and tumor spread through the bile duct [ 14 ]. Low biliary tract obstruction is caused by bile duct dilation causing stones to enter the lower common bile duct, and high biliary tract obstruction is caused by Mirizzi syndrome [ 15 , 16 ]. Patients with chronic cholecystitis are less likely to have high or low obstruction because of the absence of bile duct dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Two notable studies have examined readmission data post-PTBD. One reported a 30-day readmission rate of 20.8% and a median length of stay of nine days [9]. Another study reported a mean length of stay of 16.6 days post-PTBD [10].…”
Section: Discussionmentioning
confidence: 99%
“…Receiving chemotherapy after successful biliary drainage has a positive impact on survival after PTBD [6,7,32]. There are studies in which chemotherapy has been administered for 14-52% of gastrointestinal cancer patients after successful PTBD [21,25,[33][34][35]. In one of these studies, the incidence of cholangitis was reported [25].…”
Section: Discussionmentioning
confidence: 99%